O Sintagma Entoacional na Gaguez: evidências do PE - Cruz, Marisa (2017)
The present research examines the role of the Intonational Phrase (IP) in stuttering, based on data from two adult European Portuguese stutterers, compared with data from fluent speakers. We have analysed the prosodic organisation of controlled and spontaneous speech; the intonational structure of stuttering (types of tonal events and their distribution) and the prosodic locus of stuttering. We have identified as prosodic characteristics of stuttering: a greater density of tonal events by IP, shorter IPs, the presence of monotonal pitch accents, the anticipatory effect of pitch accents, and the ability to control only structural features related with stuttering and not pitch accent type.